USING MODERN STATISTICAL APPROACHES TO IMPROVE THE QUALITY OF FORENSIC WORK - S. Kuz'min (Теория и практика судебной экспертизы)
The author argues for implementation of statistical analysis methods and imagerecognition theory in forensic practices, algorithmization of forensic procedures, Bayesiantheorem and other tools as a way of improving the quality and efficiency of forensicoperations.